Case Report: Radiotherapy Plus Immunotherapy and Lenvatinib for the Treatment of Recurrent Hepatocellular Carcinoma With a Right Atrium and Inferior Vena Cava Tumor Thrombus - Qian, Yuting; Gong, Long; Li, Su; Mao, Kun; Li, Xianming; Liao, Guixiang (Frontiers in Oncology, 2022)
Background The treatment of hepatocellular carcinoma (HCC) with right atrium (RA) and inferior vena cava (IVC) tumor thrombi is challenging, with the standard treatment being not well established. Immunotherapy plus antiangiogenic therapy is a potentially effective treatment for patients with advanced HCC. Here, we described the case of a patient with HCC with RA and IVC tumor thrombi who achieved a successful response from radiotherapy and targeted therapy plus immunotherapy. Case Summary A 62-year-old women presented with severe bilateral lower extremity edema identified as recurrent HCC with RA and IVC tumor thrombi based on past medical history and computed tomography. The patient received palliative radiotherapy plus pembrolizumab and lenvatinib treatment and was relieved of disease symptoms of bilateral lower extremity edema. The HCC with RA and IVC tumor thrombi shrunk, and the progression-free survival of this patient was > seven months. Conclusion Tumor thrombus-directed radiotherapy plus concurrent immunotherapy and targeted therapy might be a feasible and safe approach for patients with HCC with RA and IVC tumor thrombi.